Tanggung Jawab Sosial Perusahaan dari Sudut Pandang Teori Akuntansi Positif - Yunita Putri Utami; Hans Hananto Andreas (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
The purpose of this study is to determine the effect of bonus plans, debt ratios, and political costs on the disclosure of corporate social responsibility listed on the Indonesia Stock Exchange in 2014-2016. Bonus plan is measured by return on assets (ROA), debt ratio is measured by debt to equity ratio (DER), political cost is measured by total company asset, while CSR disclosure is measured using GRI G4 standard. The sample was taken by purposive sampling method, with total sample of 288 companies. The bonus plans and political costs have a positive effect on corporate social responsibility disclosure, while the debt ratio has no effect.